CLINICAL VALUE OF MONITORING OF PROCALCITONIN LEVEL IN BLOOD DURING ARTIFICIAL LUNG VENTILATION IN NEWBORNS WITH RESPIRATORY DISTRESS SYNDOME - P. I. Mironov; V. A. Rudnov (Вестник анестезиологии и реаниматологии, 2017)
The purpose of the trial is to assess the informative value of procalcitonin level in blood when diagnosing infectious complications of lower respiratory tract during lung ventilation in newborns with respiratory distress syndrome. The trial was designed as retrospective, observatory, one-center historical monitoring. 134 newborns were included into the trial. Ventilator-associated pneumonia was diagnosed basing on CDC/NNIS criteria. Ventilator-associated tracheobronchitis was identified basing on Code LRI-BRON criteria. Sensitivity, specificity and area under operating characteristics curve were set up for patients with different concentration of procalcitonin in order to assess the threshold diagnostic value of procalcitonin level in blood. Procalcitonin level ≥ 2.1 ng/ml in a newborn with respiratory distress syndrome by the 6th day of life proves that the patient has ventilator-associated pneumonia or tracheobronchitis.